Development and validation of a questionnaire assessing expectations of the characteristics of friendly primary health services from men's perspective - Aziz, Muhammad Zikri Ab (2023)
Background: Underutilization of healthcare services may contribute to poor health status among men. This study aimed to explore men’s experiences with primary health services and their expectations regarding the characteristics of friendly primary health services in Kelantan, Malaysia, and develop a questionnaire assessing those expectations. Methodology: The study was conducted in two phases using a mixed-method approach. Phase One involved the development of a questionnaire based on an extensive literature review, in-depth interviews with adult males in Kelantan, content validation, face validation, and pilot testing. Face-to-face interviews were conducted with 15 adult males purposefully selected using a maximum variation sampling method from six governmentbased primary health facilities in Kelantan. Data were transcribed and analyzed using the thematic analysis method. The qualitative study findings were used as the basis for item generation. The procedure was followed by content validation by seven experts and face validation by ten adult males in Kelantan. Phase two involves exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to measure the questionnaire’s internal structure validity and reliability. A cross-sectional study was conducted for EFA with 280 conveniently selected participants and followed by another 280 for CFA in eight government primary health clinics in Kelantan. Results: The interview findings showed that the theme of men’s experience with existing primary health services was derived from four subthemes: provision of health services, health promotion delivery, attributes of healthcare providers, and the physical environment of the health facilities. Four other subthemes formed the theme of men’s expectations of the characteristics of friendly primary health services: meeting men’s needs in primary health services, approaching men through effective health promotion strategies, standards of a healthcare provider from a men’s viewpoint, and a comfortable physical environment for men. A new questionnaire was developed with 69 items and four domains. Following the content validation phases, items were reduced to 65, with several items with low I-CVI maintained for testing in the following process. Two items were deleted during face validation, with the remaining 63 items tested for EFA, yielding a new hypothesized model with 44 items and eight domains. The model was revised during CFA, and the best model of five domains and 39 items that met the model fitness analysis was chosen as the final questionnaire. Conclusion: The newly developed questionnaire with 39 items in five respective domains, which are the provision of health services, service time extension, health promotion and education, characteristics of healthcare providers, and physical environment of health facilities, is a valid and reliable instrument for assessing expectations of the characteristics of friendly primary health services from men’s perspective in Kelantan.